2020
DOI: 10.4148/2378-5977.7925
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Changes Across Historical Sorghum Hybrids Released During the Last Six Decades

Abstract: For the last decades, sorghum (Sorghum bicolor L. Moench) improvement in the United States (US) has been related to targeted modifications in genotype, environment, and management (G × E × M) combinations. Retrospective studies are relevant to document changes in the phenotype associated to breeding process and to explore alternatives to improve yield and its physiological associated traits. This study aims to characterize yield changes over time for hybrids with different year of release. Field trials were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…91,92 Previous studies have found that spectral data taken at flowering have produced the highest correlations with sorghum final grain yield, 45,73 which is why we chose to determine clusters with spectral data from this growth stage. Despite a trend of historical yield improvement for the hybrids used in this study, 93 hybrids in this study were not selected specifically for yield differences. Therefore, further work should be conducted among hybrids with known yield differences to determine if clusters are able to detect significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…91,92 Previous studies have found that spectral data taken at flowering have produced the highest correlations with sorghum final grain yield, 45,73 which is why we chose to determine clusters with spectral data from this growth stage. Despite a trend of historical yield improvement for the hybrids used in this study, 93 hybrids in this study were not selected specifically for yield differences. Therefore, further work should be conducted among hybrids with known yield differences to determine if clusters are able to detect significant differences.…”
Section: Discussionmentioning
confidence: 99%